Organism, Medicine, and Metaphysics
357 p.
Keywords: This Festschrift is presented to Professor Hans Jonas on the occasion of his seventy-fifth birthday, as affirmation of the contributors' respect and admiration. As a volume in the series 'Philosophy and Medicine' the contributions not only reflect certain interests and pursuits of the scholar to whom it is dedi cated, but also serve to bring to convergence the interests of the contributors in the history of humanity and medicine, the theory of organism, medicine in the service of the patient's autonomy, and the metaphysical, i.e., phenome nological foundations of medicine. Notwithstanding the nature of such personal gifts as the authors' contributions (which, with the exception of the late Hannah Arendt's, appear here for the first time), the essays also transcend the personal and serve to elaborate specific themes and theses disclosed in the numerous writings of Hans Jonas. The editor owes a personal debt of gratitude to many, including Hannah Arendt, who offered their assistance during the preparation of the volume.